Pengembangan Aplikasi Deteksi Sumber Air Tanah Menggunakan Metode Sensor Kapasitif - Ketut Doni Riyan Dinata; Tata Sutabri (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
The decline in the quality and quantity of groundwater resources is one of the biggest challenges in natural resource management in many areas. Mapping the potential of groundwater requires technology that can identify and detect the presence of water sources with high accuracy. The purpose of this study is to develop a groundwater detection application using a capacitance-based remote sensing method, which leverages the principle of capacitance changes on the soil surface due to the presence of groundwater. The capacitance sensing method was chosen because it can detect differences in capacitance between water-filled soil and dry soil. In this study, we integrate a capacitive sensor connected to electronic devices into a mobile application to visualize and analyze the data in real-time. This application aims to enable users, such as farmers and researchers, to easily monitor and detect the presence of groundwater sources at various locations with high efficiency.